Strategi Pemasaran Kewirausahaan Pada Usaha Lokafood - Alfina Rahmawati; Meisy Nanik Isdaryati; Anisyah Rahmadani; Rangga Satria; Alfito Yusuf Isa Sugihono (STIE Mahardhika, 2024)
LokaFood, one of the culinary businesses, needs to implement a marketing strategy in order to be competitive. The purpose of this study aims are to identify the internal and external factors in LokaFood and to determine the alternative strategies in LokaFood. The SWOT (Strength, Weakness, Opportunity, Threat) method was used in this study. The steps of this study were identifying the internal and external factors, and then determining the matrix of IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), position, and SWOT. The results showed that the main strength was good quality and taste; the main weakness was promotional activities that were not optimal; the main opportunity was the increasing public interest in products of LokaFood, and the main threat was more innovative competitors. The results showed that the marketing strategy to be applied by LokaFood Enterprises was the SO (Strength-Opportunity). Alternative strategies that can be used were improving the quality of LokaFood products, expanding the franchise system, especially outside Surabaya, and increasing the intensity of attractive promotion through online delivery applications.